2011
DOI: 10.1002/jcla.20449
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of IgA antitissue transglutaminase antibodies in children with type 1 diabetes mellitus

Abstract: There is an increased prevalence of IgA antitissue transglutaminase antibodies, which suggests the need to use this method as an effective first-line test in the screening of celiac disease in children with type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
2
4
0
1
Order By: Relevance
“…This recommendation is based on the study of Leeds et al [13] who observed that CD-T1D patients have a higher HbA1c level in comparison with T1D adult patients (8.2% vs. 7.5%, p =0.05). Similarly, our study confirms these findings and shows a significantly elevated median of HbA1c level in seropositive cases, in contrary to several series showing no significant difference [23, 27, 28, 31, 35, 4749].…”
Section: Discussionsupporting
confidence: 92%
“…This recommendation is based on the study of Leeds et al [13] who observed that CD-T1D patients have a higher HbA1c level in comparison with T1D adult patients (8.2% vs. 7.5%, p =0.05). Similarly, our study confirms these findings and shows a significantly elevated median of HbA1c level in seropositive cases, in contrary to several series showing no significant difference [23, 27, 28, 31, 35, 4749].…”
Section: Discussionsupporting
confidence: 92%
“…The CD prevalence among the T1DM patients in Romania was 3.9% that is comparable with European studies in adult patient with CD [29]. The IgA anti-tTG prevalence in children with T1DM was 9.2%, and sensitivity and specificity of IgA anti-tTG were 80 and 82.6% [30]. Another association of CD is with Turner syndrome, in which besides GFD, the patient requires endocrine treatment [31].…”
Section: Medical Considerationssupporting
confidence: 61%
“…Sixty‐two studies on the prevalence of CD in patients with type 1 diabetes were included in this review . The prevalence of EMA positivity ranged from 0% to 13.83%; that of elevated tTG levels ranged from 0.81% to 21.16%, while 0.40% to 12.16% showed villous atrophy, ‘flat biopsies’ or Marsh 3 histological changes.…”
Section: Resultsmentioning
confidence: 99%